"2yzdx-2xzdy-(x^2-y^2)(z-1)dz=0........................(1)"
First we take "z" to be constant. Then the equation reduces to
"2yzdx-2xzdy=0"
Divide through by "2xyz"
"\\frac{dy}{y}-\\frac{dx}{x}=0"
Integrating, we obtain;
"\\ln(\\frac{y}{x})=c\\\\\ny=xc_1"
We assume that the solution of Eqn(1) is
"y=x\\Psi(z)"
Now, let "x=\\alpha" and, therefore,
"y=\\alpha\\Psi(z) \\text{ is a solution of eqn(1).}"
Since "x=\\alpha,dx=0" . Put this into eqn(1)
"2\\alpha zdy+(\\alpha^2-y^2)(z-1)dz=0"
Divide through by "z(\\alpha^2-y^2)"
"\\frac{2\\alpha}{\\alpha^2-y^2}dy+\\left(1-\\frac{1}{z}\\right)dz=0"
Integrate through
"\\ln|\\frac{\\alpha+y}{\\alpha-y}|-\\ln|z|+z=\\ln|c| \\text{ where } c \\text{ is a constant.}"
"\\implies \\frac{\\alpha+y}{\\alpha+y}=cze^{-z}"
But "y=\\alpha \\Psi," therefore,
"\\frac{\\alpha(1+\\Psi)}{\\alpha(1-\\Psi)}=\\frac{1+\\frac{y}{x}}{1-\\frac{y}{x}}=\\frac{x+y}{x-y}=cze^{-z}"
Hence the solution is
"(x+y)e^z=c(x-y)z"
Comments
Leave a comment